Lewis H. Machen family papers - Machen, Lewis H. (Lewis Henry), 1790-1863.; Gresham, LeRoy Wiley, 1847-1865.; Machen, Arthur Webster, 1827-1919.; Machen, Caroline Webster; Machen, Emmeline; Machen, James P.; Machen, Minnie Gresham
Chiefly family correspondence of Lewis H. Machen, relating to personal matters and to national politics prior to the Civil War, especially slavery and the Compromise of 1850, and mentioning John Quincy Adams, Henry Clay, Andrew Jackson, and Daniel Webster, together with other correspondence, speeches, writings, subject files, and other papers; correspondence of Machen's son, Arthur Webster Machen (1827-1919), lawyer, of Baltimore, Md., reflecting opinion in Baltimore and in rural Maryland at the outbreak of the Civil War; farming and household account book (1833-1857) kept by Lewis H. Machen in Fairfax County, Va.; account book (1858-1889) kept by another son, James P. Machen; papers of Arthur Machen's wife, Minnie Gresham Machen, including family correspondence, diaries of her brother, LeRoy Wiley Gresham, and other papers relating to the Civil War and Reconstruction in Macon, Ga.; and receipts and financial papers, recipes, photographs, scrapbooks, clippings, printed matter, and other papers.
Other family members represented include Lewis Machen's wife, Caroline Webster Machen, and their daughter, Emmeline. Lewis and Arthur Machen's correspondents include Kendall Brooks, Joseph Cilley, John M. Clayton, Thomas Clayton, Jeremiah Day, Asbury Dickins, John Henry Eaton, Peter Force, Charles Jared Ingersoll, Andrew Jackson, Thomas Ap Catesby Jones, C.C. Langdell, William Berkeley Lewis, Walter Lowrie, Theophilus Parsons, William C. Rives, Benjamin Silliman, John Peter Van Ness, and J.D. Whelpley.
Digital version of ambrotype of LeRoy Wiley Gresham (dating between 1854 and 1865) available through the Library of Congress Web site.
Microfilm edition of account books in container 26 available
Microfilm produced from originals of account books in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Clerk of the U.S. Senate and farmer, of Fairfax County, Va.
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848.; Brooks, Kendall, -- 1821-1898.; Cilley, Joseph, -- 1791-1887.; Clay, Henry, -- 1777-1852.; Clayton, John M. -- 1796-1856.; Clayton, Thomas, -- 1777-1854.; Day, Jeremiah, -- 1773-1867.; Dickins, Asbury, -- 1780-1861.; Eaton, John Henry, -- 1790-1856.; Force, Peter, -- 1790-1868.; Ingersoll, Charles Jared, -- 1782-1862.; Jackson, Andrew, -- 1767-1845.; Jones, Thomas Ap Catesby, -- 1790-1858.; Langdell, C. C. -- 1826-1906.; Lewis, William Berkeley, -- 1784-1866.; Lowrie, Walter, -- 1784-1868.; Parsons, Theophilus, -- 1797-1882.; Rives, William C. -- 1793-1868.; Silliman, Benjamin, -- 1779-1864.; Van Ness, John Peter, -- 1770-1846.; Webster, Daniel, -- 1782-1852.; Whelpley, J. D. -- 1863-; Gresham family; Machen family; Agriculture -- Virginia -- Fairfax County; Compromise of 1850.; Reconstruction (U.S. history, 1865-1877) -- Georgia -- Macon; Slavery -- United States; Baltimore (Md.) -- History -- Civil War, 1861-1865.; Georgia -- History -- Civil War, 1861-1865.; Macon (Ga.) -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Public opinion; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- Politics and government -- 19th century; Farmers; Public officials